Pengaruh Kompensasi Dan Komitmen Organisasi Terhadap Kinerja Terhadap Disiplin Kerja Pada Dinas Perdagangan Mandailing Natal - Rahmad Hidayat; R. Sabrina; Fajar Pasaribu (Forum Kerjasama Pendidikan Tinggi, 2023)
The purpose of this study was to identify and analyze the effect of additional salary on employee performance, the effect of organizational commitment on employee performance, the effect of additional salary on work discipline, the effect of organizational commitment on work discipline, and its effect on work discipline. work discipline. . Discipline on employee performance, the effect of additional salary on employee performance through work discipline, and the influence of organizational commitment on employee performance through work discipline. This study uses relational research with a sample of 66 participants who are employees of the Mandailing Natal Commercial Office. Interviews and annotation list data collection techniques such as surveys and data analysis techniques Partial Least Square (SmartPls) to test the seven hypotheses proposed in this study. The results showed that extra pay had a significant effect on employee performance, organizational commitment had a significant effect on employee performance, extra pay had a significant effect on employee performance, work discipline, organizational commitment had a significant effect on work discipline, and work discipline was very influential. have a significant impact on business discipline. little effect on work discipline. significant effect on employee performance, extra pay significant effect on performance. Employee work discipline (ie mediation work discipline) while organizational commitment has a significant effect on employee performance through medium work discipline (ie work discipline).